Organizational Commitment and Independence Among Canadian Managers - Baba, Vishwanath; Knoop, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
A model of organizational commitment linking the antecedents and consequence of commitment with organizational independence as a moderator is proposed and tested.